When Pain Relief Turns Perilous: A Case Report on Paracetamol Dependence, Polypharmacy, and Severe Drug-Induced Liver Injury - Kadek Nova Adi Putra; Bgs Gde Ariesta Darmahendra (Archives of The Medicine and Case Reports, 2025)
Drug-induced liver injury (DILI) from long-term therapeutic paracetamol use, especially when complicated by psychological dependence, and concurrent atorvastatin therapy within a polypharmacy setting is an uncommon but serious clinical concern. This report details such a case, emphasizing the diagnostic challenges and management. A 58-year-old woman with a 20-year history of dependence on paracetamol (500-1500 mg daily) and 12 years of atorvastatin use (20 mg daily) amidst other chronic medications (levothyroxine, candesartan, clopidogrel), presented with bleeding gums, abdominal discomfort, nausea, and weakness. Laboratory investigations revealed markedly elevated liver enzymes (SGPT 3913 U/L, SGOT 5863 U/L), severe thrombocytopenia (17 x 10³/L), and elevated Gamma GT (449 U/L). Viral hepatitis markers were negative. Paracetamol and atorvastatin were discontinued. Significant clinical and biochemical improvement followed, with SGOT/SGPT levels decreasing to 184/283 U/L by day six. In conclusion, the Roussel Uclaf Causality Assessment Method (RUCAM) indicated paracetamol and atorvastatin as "probable" causes of DILI. This case underscores the potential for severe hepatotoxicity from long-term therapeutic use of common medications, especially in polypharmacy and when psychological factors influence drug consumption. Vigilant monitoring and causality assessment are crucial in such complex scenarios.